Perbaikan Proses dan Alat Produksi Jamu Coro Minuman Khas Demak pada UMKM SITU JAMU di Desa Berahan Kulon, Kecamatan Wedung, Kabupaten Demak - Saputro, Herman; Fitriana, Laila; Bugis, Husin; Ranto, Ranto; Muslim, Riyadi (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2023)
Berahan Kulon Village, apart from being known as a fishing and fish farming village, also has Micro, Small and Medium Enterprises (MSMEs) that produce herbal drinks known as Jamu Coro. Jamu Coro is made from rice flour and spices such as ginger, lemongrass, cinnamon, coconut sugar and coconut milk. This traditional drink has existed since the days of the Bintoro Sultanate and was served at meetings or events at the Demak Bintoro palace at that time. The existence of wedang herbal medicine coro is still maintained and preserved by the community. They are the conservators of herbal coro in Berahan Kulon Village by making herbal products in powder form. These MSMEs have problems with production equipment that is still completely manual and the production process is not good or hygienic. The problem is the quality of coro herbal products which are in the form of non-uniform powder. SMEs also find it difficult to develop large orders. Based on the society team at Sebelas Maret University, it intends to help SMEs Situ Jamu through the Community Partnership Program. It is hoped that it can improve the quality and quantity of herbal coro in powder form and improve the economy in Berahan Kulon. An output will be obtained in the form of appropriate technology for supporting the production of coro herbal medicine